Description des pratiques pédagogiques différenciées mises en place par les enseignants de musique à l’égard des élèves du primaire présentant un trouble d’anxiété - Blouin, Martin; Joly, Jacques; Nootens, Pascale (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Inclusion of students with anxiety issues in music classes is a challenge for teachers. To ensure the success of all students, the school must look into the means available in educational environments. Differentiated instruction appears as a preferred measure. However, the studies reported mention that teachers seldom use them systematically. In this context, this article aims to describe the differentiated pedagogical practices implemented within music classes. To achieve this, self-reported data from 101 respondents were analyzed. Keywords: differentiated instruction, teaching practices, music teaching, anxiety disorders, elementary students